Equity zombies in Canada’s blue economy: a critical feminist analysis for equitable policy implementation - Knott, Christine; Fusco, Leah M.; Daly, Jack; Andrews, Evan; Singh, Gerald Gurinder (Frontiers in Marine Science, 2024)
Introduction Ocean equity is a key aim of blue economy frameworks globally and is a pillar of the international High Level Panel for A Sustainable Ocean Economy. However, the Panel offers only a general definition of ocean equity, with limited guidance for countries. Canada, as a party to the High Level Panel’s blue economy agenda, is developing its own blue economy strategy, seeking to reshape its ocean-based industries and advocate for new ones. How equity will be incorporated across scales is not yet known but has implications for how countries like Canada will develop their ocean-based industries. This raises important questions, including what are Canada’s equity commitments in relation to its blue economy and how will they be met? Currently, the industries identified in Canada’s emerging blue economy narratives are governed through both federal and provincial legislation and policies. These will shape how equity is implemented at different scales. Methods In this paper, we examine how the term equity is defined in relevant federal and provincial legislation and look to how understandings of equity found in critical feminist, environmental justice, and climate justice scholarship could inform policy and its implementation within Canada’s blue economy. We focus on two industries that are important for Canada’s blue economy: offshore oil and marine salmon aquaculture in the Canadian province of Newfoundland and Labrador. We investigate how existing legislation and policy shapes the characterization, incorporation, and implementation of equity in these industries. Results and discussion Our analysis highlights how a cohesive approach to ocean equity across the scales of legislation and policy is needed to ensure more robust engagement with social and environmental equity issues in blue economy discourse and implementation.